Do a Few Months of Compulsory Schooling Matter? : The Education and Labour Market Impact of School Leaving Rules - Emilia Del Bono; Fernando Galindo-Rueda (Institute for the Study of Labor (IZA), 2004)
This paper contributes to the understanding of how compulsory schooling regulations affect educational attainment and subsequent labour market outcomes. It uses valuable information from a natural experiment driven by rules that allow for variation in legal dropout dates. Since the school leaving rule bites in the middle of a school year cohort, our identification approach is immune to other relative age/peer effects. Information on the precise month of birth enables us to show that students compelled to stay on in education as a result of this compulsory school leaving rule attain higher qualification levels and see their participation and employment probability as adults enhanced. We show that the estimated genuine impact of attaining an academic qualification on participation and employment is always statistically significant, in particular for women, although IV coefficients are usually below OLS estimates.
Keywords: I2; J24; C13; 330; education; school leaving rules; instrumental variables; participation; employment; Absolventen; Schulrecht; Bildungsniveau; Bildungsertrag; Schätzung; Vereinigte Staaten; Schulpflicht